2011
DOI: 10.1007/s10482-011-9570-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional diversities of bacterial communities in the rhizosphere of Arachis hypogaea

Abstract: Bioinoculants are environmentally friendly, energy efficient and economically viable resources in sustainable agriculture. Knowledge of the structure and activities of microbial population in the rhizosphere of a plant is essential to formulate an effective bioinoculant. In this study, the bacterial community present in the rhizosphere of an important oilseed legume, Arachis hypogaea (L.) was described with respect to adjoining bulk soil as a baseline control using a 16S rDNA based metagenomic approach. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
13
1
1
Order By: Relevance
“…The bacterial diversity and abundance in rhizosphere of different plants and crops was studied using fingerprinting techniques and 16S rRNA gene as a target (Chauhan et al, 2011;Costa et al, 2005;Haldar et al, 2011;Sharma et al, 2005;Smalla et al, 2001). Previously, bacterial diversity was studied from groundnut rhizosphere using 16S rRNA restriction fragment length polymorphism (RFLP) under laboratory conditions by both culture dependent and independent methods (Haldar et al, 2011). Haldar et al (2011) reported Proteobacteria and Bacteroidetes as the dominant phyla while in the present study, Firmicutes was found abundant followed by Proteobacteria, Actinobacteria and Bacteroidetes (Supplementary Table S1).…”
Section: Number Of Clonesmentioning
confidence: 60%
See 3 more Smart Citations
“…The bacterial diversity and abundance in rhizosphere of different plants and crops was studied using fingerprinting techniques and 16S rRNA gene as a target (Chauhan et al, 2011;Costa et al, 2005;Haldar et al, 2011;Sharma et al, 2005;Smalla et al, 2001). Previously, bacterial diversity was studied from groundnut rhizosphere using 16S rRNA restriction fragment length polymorphism (RFLP) under laboratory conditions by both culture dependent and independent methods (Haldar et al, 2011). Haldar et al (2011) reported Proteobacteria and Bacteroidetes as the dominant phyla while in the present study, Firmicutes was found abundant followed by Proteobacteria, Actinobacteria and Bacteroidetes (Supplementary Table S1).…”
Section: Number Of Clonesmentioning
confidence: 60%
“…This indicates a high diversity in groundnut rhizosphere, which was supported by both parametric and non-parametric diversity indices ( Table 2). The bacterial diversity and abundance in rhizosphere of different plants and crops was studied using fingerprinting techniques and 16S rRNA gene as a target (Chauhan et al, 2011;Costa et al, 2005;Haldar et al, 2011;Sharma et al, 2005;Smalla et al, 2001). Previously, bacterial diversity was studied from groundnut rhizosphere using 16S rRNA restriction fragment length polymorphism (RFLP) under laboratory conditions by both culture dependent and independent methods (Haldar et al, 2011).…”
Section: Number Of Clonesmentioning
confidence: 99%
See 2 more Smart Citations
“…OTU 71090 had a 98 % similarity with GU245918.1 and a 97 % similarity with GU245920.1, which stand for Clostridium sp. [25] clones. Some Clostridium species are human pathogens related with tetanus or gas gangrene diseases, among others [26,27].…”
Section: Relative Abundance and Diversity Of The Demon Bioreactormentioning
confidence: 99%